Effect of Economic Growth on Well-Being in Sub-Saharan Africa: Does Institutional Quality Matter? - Séraphin, Prao Yao; Valery, Koffi Mounoufié (International Journal of Economics and Financial Issues, 2025)
This study analyzes the role of institutional quality in the relationship between economic growth and improved well-being in Sub-Saharan Africa over the period 2007-2021. This study collected data from the World Bank and Legatum Prosperity Index websites for 35 Sub-Saharan African countries. Methodologically, the study uses the generalized method of moments (GMM) in a two-stage system. The results reveal that economic growth reduces the well-being of populations, while institutional quality improves it. Furthermore, institutional quality mitigates the negative effect of economic growth on the well-being of populations. However, this effect is more pronounced in Anglo-Saxon countries than in French-speaking countries. Similarly, there are minimum thresholds of institutional quality beyond which economic growth contributes to improving the well-being of populations in Sub-Saharan Africa.